Study on Psychiatric Disorders and Their Medical-Social Consequences in Patients with Amyotrophic Lateral Sclerosis and Members of Their Families - Levitsky, Gleb N.; Levitsky, Andrey S.; Gilod, Vadim M. (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
A total of 118 ALS patients and 97 family members were evaluated. Psychiatrists observed all of the patients and their relatives. Study objectives were to detect anxiety, depression, habitual intoxications, frontotemporal dysfunction, unjustified expenses and poor collaboration with physicians among ALS patients and their families. The Hamilton Depression Scale (for patients and their families) and the frontotemporal dementia scale were used in the evaluation (for patients).Psychiatric illnesses were discovered in 101 ALS patients (85%) and 51 family members (52.5%) (significantly more frequently in ALS patientsp<0.05). In ALS patients, the spectrum of situation-mediated illnesses was rather evenly represented, with no apparent predominance of situation-mediated depression.Rare occurrences of ALS combined with endogenous psychological problems have been reported.Frontotemporal cognitive deficits reaching the degree of dementia were seen in 4.2 percent of cases in 33 individuals (28 percent). Only situation-mediated psychiatric problems with a clear predominance of anxiety (28 percent, p<0.05 ) were seen among family members of ALS patients. Habitual intoxication affected 49 ALS patients (41.5%) and 80 members of their families (82.4%) (significantly more frequently in family members, p<0.05). Due to the high incidence of anxiety problems, people refuse to cooperate with professional physicians (73-76%), reject aggressive treatment approaches (74.5%), approach fraudsters, and bear the burden of unjustifiable spending (29.6 percent of cases). Consistent patronage of ALS patients' families by neurological and psychotherapeutic services, with involvement of psychiatrists and narcologists in individual cases, is recommended, as this can increase the number of life-saving procedures performed at ALS and improve the quality of life of patients and their families.